2010
DOI: 10.1161/circulationaha.109.915215
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Accelerates Transition to Heart Failure With Preserved Ejection Fraction Via “Nongenomic Effects”

Abstract: Background-Mechanisms promoting the transition from hypertensive heart disease to heart failure with preserved ejection fraction are poorly understood. When inappropriate for salt status, mineralocorticoid (deoxycorticosterone acetate) excess causes hypertrophy, fibrosis, and diastolic dysfunction. Because cardiac mineralocorticoid receptors are protected from mineralocorticoid binding by the absence of 11-␤ hydroxysteroid dehydrogenase, salt-mineralocorticoid-induced inflammation is postulated to cause oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 48 publications
3
75
1
1
Order By: Relevance
“…function with MR blockade independently of effects on blood pressure (15,17,18). Although previous work on blood pressure-independent effects of MR antagonism and diastolic function have supported an essential role for salt and/or nephrectomy in promoting MR-dependent cardiac fibrosis and diastolic dysfunction (2,15,17,18,29,31,38), this is the first such study in a RAAS-dependent model. Because we began treatment before the onset of diastolic dysfunction, our data further suggest that low-dose Sp treatment is effective at preventing the development of diastolic dysfunction through improvements in myocardial fibrosis and oxidant stress in young transgenic rats.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…function with MR blockade independently of effects on blood pressure (15,17,18). Although previous work on blood pressure-independent effects of MR antagonism and diastolic function have supported an essential role for salt and/or nephrectomy in promoting MR-dependent cardiac fibrosis and diastolic dysfunction (2,15,17,18,29,31,38), this is the first such study in a RAAS-dependent model. Because we began treatment before the onset of diastolic dysfunction, our data further suggest that low-dose Sp treatment is effective at preventing the development of diastolic dysfunction through improvements in myocardial fibrosis and oxidant stress in young transgenic rats.…”
Section: Discussionmentioning
confidence: 77%
“…Both cardiac myocytes and fibroblasts express MRs with a high affinity for aldosterone (17,32,38). However, the development of interstitial fibrosis and diastolic dysfunction by aldosterone actions on the MR occur when the renin-angiotensin-aldosterone system (RAAS) is inappropriately activated relative to salt intake, i.e., in the absence of salt deprivation (30,32).Inappropriate activation of the RAAS through aldosterone actions on the MR have been shown to promote the development of diastolic dysfunction through putative nongenomic actions including the generation of oxidative stress in models of chronic pressure overload (18,22,38). Oxidative stress is known to impair metabolic signaling pathways that regulate cardiac remodeling, LV hypertrophy (LVH), and diastolic dysfunction through interstitial fibrosis (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 An excess of mineralocorticoid causes cardiac hypertrophy, fibrosis and diastolic dysfunction. 30,31 In this study, we found for the first time that the plasma concentration of aldosterone increased after I/R partially through the upregulation of plasma renin activity and that benidipine treatment effectively inhibited this response in vivo. Aldosterone is produced mainly by the adrenal cortex in response to increased potassium or angiotensin II.…”
Section: Discussionmentioning
confidence: 62%